Review of Hair Follicle Dermal Papilla cells as in vitro screening model for hair growth - Madaan, Alka; Verma, Ritu; Singh, Anu T.; Jaggi, Manu (International journal of cosmetic science, 2018)
Hair disorders such as hair loss (alopecia) and androgen dependent, excessive hair growth (hirsutism, hypertrichosis) may impact the social and psychological well‐being of an individual. Recent advances in understanding the biology of hair have accelerated the research and development of novel therapeutic and cosmetic hair growth agents. Preclinical models aid in dermocosmetic efficacy testing and claim substantiation of hair growth modulators. The in vitro models to investigate hair growth utilize the hair follicle Dermal Papilla cells (DPCs), specialized mesenchymal cells located at the base of hair follicle that play essential roles in hair follicular morphogenesis and postnatal hair growth cycles. In this review, we have compiled and discussed the extensively reported literature citing DPCs as in vitro model to study hair growth promoting and inhibitory effects. A variety of agents such as herbal and natural extracts, growth factors and cytokines, platelet‐rich plasma, placental extract, stem cells and conditioned medium, peptides, hormones, lipid‐nanocarrier, light, electrical and electromagnetic field stimulation, androgens and their analogs, stress‐serum and chemotherapeutic agents etc. have been examined for their hair growth modulating effects in DPCs. Effects on DPCs’ activity were determined from untreated (basal) or stress induced levels. Cell proliferation, apoptosis and secretion of growth factors were included as primary end‐point markers. Effects on a wide range of biomolecules and mechanistic pathways that play key role in the biology of hair growth were also investigated. This consolidated and comprehensive review summarizes the up‐to‐date information and understanding regarding DPCs based screening models for hair growth and may be helpful for researchers to select the appropriate assay system and biomarkers. This review highlights the pivotal role of DPCs in the forefront of hair research as screening platforms by providing insights into mechanistic action at cellular level, which may further direct the development of novel hair growth modulators. Résumé Les problèmes capillaires, tels que la perte de cheveux (alopécie) et la croissance excessive des cheveux dépendante des androgènes (hirsutisme, hypertrichose), peuvent avoir un impact sur le bien‐être social et psychologique de la personne. De récentes avancées dans la connaissance de la biologie des cheveux ont accéléré la recherche et le développement de nouveaux agents thérapeutiques et cosmétiques pour la croissance des cheveux. Les modèles précliniques contribuent aux analyses d'efficacité dermo‐cosmétiques et à la justification des allégations de modulateurs de croissance capillaire. Les modèles in vitro visant à étudier la croissance des cheveux utilisent les cellules du derme papillaire (Dermal Papilla Cells, DPC) du follicule pileux, des cellules mésenchymateuses spécialisées situées à la base du follicule pileux, qui jouent un rôle essentiel dans la morphogenèse du follicule pileux et les cycles de croissance capillaire post‐natals. Dans cette revue, nous avons compilé et examiné la vaste littérature rapportée, mentionnant les DPC comme modèle in vitro pour étudier les effets stimulateur et inhibiteur de la croissance capillaire. Divers agents, tels que les extraits naturels et des extraits de plantes, les facteurs de croissance et les cytokines, le plasma riche en plaquettes, l'extrait de placenta, les cellules souches et le milieu conditionné, les peptides, les hormones, les nanovecteurs lipidiques, la lumière, la stimulation du champ électrique et électromagnétique, les androgènes et leurs analogues, les sérums anti‐stress et les agents chimiothérapeutiques, entre autres, ont été examinés pour leurs effets modulateurs de la croissance capillaire au niveau des DPC. Les effets sur l'activité des DPC ont été déterminés à partir de niveaux non traités (basiques) ou induits par le stress. La prolifération cellulaire, l'apoptose et la sécrétion de facteurs de croissance ont été incluses comme marqueurs du critère d’évaluation primaire. Les effets sur un large éventail de biomolécules et voies mécanistiques jouant un rôle clé dans la biologie de la croissance des cheveux ont également été étudiés. Cette revue exhaustive et approfondie résume les informations et connaissances actualisées concernant les modèles de sélection basés sur les DPC pour la croissance des cheveux, et peut permettre aux chercheurs de sélectionner le système de test et les biomarqueurs appropriés. Cette revue met en évidence le rôle fondamental des DPC au premier plan de la recherche capillaire comme plateformes de sélection, en fournissant un aperçu du mécanisme au niveau cellulaire, ce qui peut orienter encore davantage le développement de nouveaux modulateurs de croissance capillaire.